(untitled)
This study was an attempt to investigate the self-esteem and job satisfaction of teachers as a function of types of teacher and institutions. To collect data, participants were selected purposively, Total 120 respondents were selected. Among them 60 were college teachers (30 were from government and 30 from non-government college). In addition, 60 were school teachers (30 were from government and 30 from non-government schools) were selected. The Bangla version of "Job Satisfaction Scale" (Rahman, 2003) and "Self-esteem Scale" (Ilyas 2003) were used to measure job satisfaction -and self-esteem of the teachers. Data were analyzed by mean, standard deviation, Pearson Product Moment Correlation and two-way analysis of variance (ANOVA). The findings of the presentstudy showed that Government teachers are found having significantly more self-esteemed (F= 5:7.1